Digital Media and Students’ Writing Ability - Liando, N V F; Martha, S (Universitas Negeri Manado, 2019)
With the development of information and technology nowadays, schools need to adapt and make changes. This research aims to investigate the application of digital media in improving students’ ability in writing a report text. This research was done in one class at one high school in North Sulawesi. The eighth-grade students consist of 30 students. In this study, digital media used was power point presentation. In collecting the data, the researcher worked collaboratively with the English teachers in the school in which Classroom Action Research was employed. The research was conducted in two cycles which there were four steps each cycle: planning, observing, acting and reflecting. The data were collected through observation check list and conducting the test after implementing each cycle. The result of each cycle showed that students writing ability was increased. The result of test in cycle 1: 76.73 and in cycle 2: 81.06. This result leads to a conclusion that students’ ability in writing report text increased. Thus, it could be recommended that writing report text should be taught using an interesting digital media like power point presentation Keywords: Digital media, Writing Skill, report text, CAR.